Earlobe sarcoidosis - Vorselaars, A.D.M.; Keijsers, R.G.M.; Grutters, et al., J.C. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2012)
Background: Infliximab, a TNF-α blocking agent, is an upcoming therapeutic option for cases of refractory sarcoidosis. In pulmonary sarcoidosis, changes imaged by 18F-FDG-PET during infliximab treatment in sarcoidosis patients correlate with signs of clinical improvement. Design: Case-report. Results and conclusions: A patient with severe earlobe sarcoidosis, treated with infliximab, is presented. This case shows that even relatively small extrapulmonary localisations of sarcoidosis can be visualised by 18F-FDG-PET, and that a decrease of FDG-uptake correlates well with clinical improvement on infliximab treatment.